Cladistic analysis of Subfamily Bruchomyiinae (Diptera: Psychodidae) - Wagner, Rüdiger; Stuckenberg, Brian (Zootaxa, 2016)
Subfamily Bruchomyiinae is comprised of 60 species and has been referred to as the most primitive within the Psychodidae. The assumed sister-group relationship with Phlebotominae is based on ecological constraints of their environment. A cladistics analysis based on 29 characters and 52 species revealed the distinction of an Old World clade characterized by males with elongate, narrow vasa deferentia, and a New World clade with males having shorter and basally widened vasa deferentia. The Old World clade consists of the genera Nemopalpus Macquart (9 species), and Eutonnoiria Alexander (1 species). The New World clade includes Bruchomyia Alexander (10 species), Boreofairchildia genus nov. (13 species), Laurenceomyia genus nov. (5 species), and Notofairchildia genus nov. (15 species). Parsimony and Bayesian analyses resulted in trees that generally support this generic classification; however, with some species groups less resolved. Diagnostic features for genera are provided. In contrast to the other New World genera, Notofairchildia is paraphyletic with the provisional inclusion of at least the Australasian taxa.